Analisis Korelasi Kemampuan Berpikir Divergen dengan Kreativitas Ilmiah pada Mahasiswa Calon Guru IPA - Suwito Singgih (Journal on Education, 2024)
This research aims to analyze the relationship between divergent thinking abilities and scientific creativity. That creativity is stated to originate from divergent and convergent thinking. Quantitative descriptive methods with a correlation approach were used in the research. A total of 100 prospective science teacher students were research subjects using random sampling techniques. Measuring divergent thinking abilities uses an instrument that adapts Graphic Convergent Thinking (GCT), consisting of the Gestalt Completion Test (GCT) and Snowy Picture Test (SPT). The scientific creativity instrument adapts the Scientific Creativity Test (SCT), which contains the dimensions of unusual use, problem finding, product improvement, creative imagination, problem solving, science experimentation, and product design. Correlation analysis was carried out using the Pearson correlation test. The results of the correlation test analysis obtained a Pearson correlation index of 0.932 with a significance of 0.000. These results state that divergent thinking has a very strong correlation with scientific creativity. Divergent thinking gives individuals the ability to produce many solutions with many ways of solving problems. The accuracy of the solution provided depends on the initial knowledge or information that the individual already has. Divergent thinking does not always produce new solutions.